Response awareness and instructional self-efficacy: influences on intent. (25th September 2019) - Mutchler, Leigh A.
Abstract : Purpose: This paper aims to examine the influence of response awareness on behavioral intent, and introduces instructional self-efficacy, a construct rarely examined within the context of information security (ISec). Design/methodology/approach: A Web-based survey was conducted and a total of 211 valid responses were analyzed. The relationships among response awareness, instructional self-efficacy and behavioral intent were examined through a three-phase structural equation modeling analysis. Findings: The results indicate that even at low levels, response awareness has a strong influential effect on the behavioral intent to perform the secure response and on the self-efficacy to instruct others to perform the response. Instructional self-efficacy was also found to be a significant predictor of behavioral intent to perform the response. Finally, evidence was found indicating instructional self-efficacy fully mediates the response awareness to the behavioral intent relationship. Research limitations/implications: Because of the characteristics of the population, the focus on a single ISec response and the dependent variable of behavioral intent rather than actual behavior, the generalizability of the findings is impacted. Practical implications: The results contribute to practice by confirming the importance of response awareness and of instructional self-efficacy within an ISec context. Specific implications include the indication that informal communications about ISec issues among peers should be encouraged and that instructional self-efficacy should be targeted within ISec awareness training programs. Originality/value: This paper's parsimonious model defined response awareness as vicarious experience with a response and presented instructional self-efficacy, a construct novel to ISec studies that was found to be a significant influence within the relationship between response awareness and behavioral intent.